IMPLEMENTASI KOMPETENSI PEDAGOGIK GURU PAI DALAM PEMBELAJARAN DI SEKOLAH DASAR NEGERI - Saripudin; Dudung Ali Nurdin; Wiwik Dyah Aryani (STAI Pelabuhan Ratu, 2025)
This research was motivated by the importance of pedagogic competence of pie teachers in learning. The purpose of this study is to determine the planning and implementation of the implementation of pedagogic competence of pai teachers at SDN 01 Pangalengan. This research is located at SDN 01 Pangalengan, Bandung Regency. The instruments used in this study were interview guidelines, observation guidelines, and documentation studies. The steps for implementing the research are collecting interview data from resource persons who are then processed, the results of observational observations in the field, collecting available documents. The results of this study show that the planning of the implementation of pedagogical competence of PAI teachers at SD Negeri Pangalengan is in accordance with existing theories and concepts as well as established government regulations, namely 1) Fulfillment of needs; 2) Setting training goals; 3) Determination of training programs; 4) Implementation of training; and 5). Assessment of the implementation of training programs. The implementation of pedagogical competence of PAI teachers at SD Negeri Pangalengan in learning is evidenced by mastery of the characteristics of students from physical, moral, social, cultural, emotional and intellectual aspects